Information and psychological vulnerability of employees of internal affairs bodies with different levels of stability and fatigue - K.V. Zlokazov (Психология и право)
The article with the involvement of empirical material reveals issues of information-psychological vulnerability and psychological stability in the context of fatigue of employees of internal affairs bodies. The purpose of the study is to identify the relationship between fatigue and psychological stability and information-psychological vulnerability of employees and to establish differences in the severity of these parameters among employees with different levels of fatigue. The respondents were 271 employees of the internal affairs bodies. Among the surveyed 97 cadets of the fifth year of full-time education and 89 students of the initial training of the St. Petersburg University of the Ministry of Internal Affairs of Russia, as well as 85 current employees with service experience from 3 to 7 years who underwent advanced training at the SPBU MVD of Russia. We used psychodiagnostic techniques: Subjective assessment of the level of personality fatigue, Scale of psychological stability of the personality and Scale of information and psychological vulnerability. It has been established that an increase in fatigue is accompanied by an increase in information and psychological vulnerability and a decrease in psychological stability. It was found that in a group of employees with a low level of fatigue, indicators of information and psychological vulnerability are at a low level, while psychological stability is at a high level. In those surveyed with a high level of fatigue, vulnerability indicators are expressed at a high level, and resilience - at a low level. Whereas in the group of subjects with a moderate level of fatigue, indicators of information and psychological vulnerability and resilience are expressed at an average level.